Patient safety and interprofessional education: A report of key issues from two interprofessional workshops. Issue 2 (4th March 2017) - Anderson, Elizabeth S.; Gray, Richard; Price, Kim
ABSTRACT: This article presents the outcomes of two workshops which explored historical and recent issues on patient safety that directly relate to leaders in the interprofessional field. The article considers the impact of flattened team-based structures where collaborative working constantly considers safe patient-centred high-quality care. These issues are mainly rooted in changes within a UK context, but the historical case studies present situations which could enlighten and enliven discussions of patient safety in an international context. The article was sparked by discussion of recurrent themes in healthcare that have undermined the abilities of medical practitioners to adequately manage hazard in clinical care settings throughout modern history. Examining the issues that confront healthcare practitioners and care workers in their dealings with patients and clients, such as the aged or the severely disabled, can reveal commonalities across global healthcare settings, in the past and present, that provide a useful tool in facilitating the goals of interprofessional education (IPE). The potential of IPE has links to both how professionals respond together to care situations and involve the general public in shared health understandings. The outcomes focus on how to ensure ministrations where optimal team-based collaborative care is recognised and constantly sought. We conclude that IPE has much to offer in this arena and more evidence of impact here is well worth pursuing.